A Novel Endoscopic-Assisted Harvesting of Pedicled Freestyle Fasciocutaneous Flaps. Issue 8 (February 2015) - Huang, Jen-Wu; Lin, Yi-Ying; Wu, Nai-Yuan; Yen, David Hung-Tsang
Abstract : Abstract: The endoscopy-assisted technique has been demonstrated in harvesting muscle flaps; however, for pedicled freestyle fasciocutaneous flaps, few studies have applied this technique. We present a surgical procedure utilizing endoscopic-assisted method to identify the perforators of pedicled freestyle fasciocutaneous flaps for the reconstruction of soft tissue defects. From August to December 2012, 9 consecutive patients underwent endoscopic-assisted harvesting of fasciocutaneous flaps for the reconstruction of soft tissue defects. All of the defects were caused by trauma with tendon or bone exposure. Postoperatively, all patients were requested to return for outpatient follow-up visits for at least 3 months. The age of the 9 patients (8 men and 1 woman) ranged from 20 to 79 years (median 59 years). The defects ranged in size from 2 × 2 to 6 × 8 cm 2 . Two patients received anterolateral thigh transmuscular perforator flaps, 5 patients received fibular septocutaneous perforator flaps, and 2 patients received medial gastrocnemius transmuscular perforator flaps. The median incision length was 10 cm, and the median operative time was 120 minutes. None of the patients had intraoperative complications, and intraoperative bleeding was minimal (<50 mL). At the end of the 3-month follow-up period, none of the patients had any complications on either recipient or donor site, including total or partial necrosis of the flaps, flap dehiscence, hematomas, seromas, wound infections, or any conditions that indicated additional unplanned operative procedures. All of the patients had surviving flaps. Our results demonstrated that the endoscopic-assisted method could be a valuable and reliable alternative in harvesting pedicled freestyle fasciocutaneous flaps.